Analisis Fenomena Elektrohidrodinamik pada Permukaan Minyak Silikon Menggunakan Plasma Lucutan Pijar Korona Positif - Rahayu, Sri; Azam, M.; Triadyaksa, Pandji; Nur, Muhammad (BERKALA FISIKA, 2007)
The aim of this research is analysis electrohydrodynamic phenomenon deformation of oil silicon surface by technology of positive corona glow discharge plasma which generated by plasma generator system with point-to-plane electrodes geometry configuration. Variation of voltage and distance between electrodes had been treated to surface of silicon oil. Electrohydrodynamic phenomenon deformation in this research is caused by polarization and ion wind. Ionic wind would be happened if applied voltage over the corona threshold that was 2.6 kV. Graph current of saturation corona unipolar for variation voltage, being formed semi-parabolic equation while the variation of distance between electrodes, being formed linear equation. The hole diameter at variation voltage was influenced by electrics field intensity and momen dipole strength. The hole diameter at variation of distance between electrode was influenced by parabolic angle of electrics line field. The oil velocity for back to initial position is different. Velocity would be go down if the voltage progressively go up and velocity would be go up if the distance between electrode progressively go up.